1997
DOI: 10.1021/jp970470o
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Energy and Electron-Transfer Reactions of the Triplet State of 1-Nitronaphthalene:  A Laser Flash Photolysis and Time-Resolved Resonance Raman Study

Abstract: A laser flash photolysis and time-resolved resonance Raman study of 1-nitronaphthalene (1NN) in sodium nitrite and trans-stilbene (tS) solution, in both polar and nonpolar solvents, is reported. The transient absorption data suggest that 1NN acts as an electron acceptor with nitrite ions and tS in polar solvents but undergoes energy transfer to tS in nonpolar solutions. At high concentrations of tS the electron-transfer reaction leads ultimately to the formation of a dimer radical cation (tS2)•+. We report her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 56 publications
1
37
0
1
Order By: Relevance
“…The nature of the 1NN triplet state has been the subject of discussion: some authors suggested a π -π* state, others a n -π* state, while some even suggest that the lowest energy state is correlated with the increase in solvent polarity, switching from n -π* to π -π*. Fournier and co-workers 27 demonstrated that in polar solvents (e.g. water) the dipolar π -π* should be more stable than n -π*.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the 1NN triplet state has been the subject of discussion: some authors suggested a π -π* state, others a n -π* state, while some even suggest that the lowest energy state is correlated with the increase in solvent polarity, switching from n -π* to π -π*. Fournier and co-workers 27 demonstrated that in polar solvents (e.g. water) the dipolar π -π* should be more stable than n -π*.…”
Section: Resultsmentioning
confidence: 99%
“…Although the halogen radicals can initiate a set of catalytic cycles capable of destroying ozone 26 or of oxidizing organic compounds (R2 and R3), to our knowledge only a limited number of studies have investigated their formation via photosensitized reactions of organic compounds in the atmospheric aqueous phase. The interaction between the excited state of 1NN ( 3 1NN) and halides has previously been reported in ethanol-water solution 27 . The H-atom abstraction between 3 1NN and ethanol, reported by the cited authors as the main reaction, suggests that the interaction between 1NN and halides could be affected by a solvent-triplet state interaction.…”
Section: Introductionmentioning
confidence: 83%
“…ion pairs and exciplexes is still unknown. Time-resolved vibrational spectroscopy, which has been very scarcely used in this field [119][120][121][122], should give a new insight. Time-resolved multidimensional IR spectroscopy, which is just emerging [123,124], might prove to be a powerful tool to investigate the geometry of these bimolecular complexes.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Because of this efficient ISC and thus large triplet yield, the photochemistry of most nitroaromatic compounds essentially takes place from the T 1 state. [6][7][8][9][10] More recently, the fluorescence decays of a series of polycyclic nitroaromatic hydrocarbons such as 1-nitronaphthalene, 9-nitroanthracene, and 1-nitropyrene in methanol have been shown to be ultrafast, with average time constants on the subpicosecond time scale. 11,12 These very small lifetimes have been ascribed to highly efficient ISC, and as a result, these compounds can be considered as the organic molecules with the fastest ISC.…”
Section: Introductionmentioning
confidence: 99%